Pelas páginas de Zero Hora, o jornalismo público (des)coberto - Pérsigo, Patrícia Milano (2015)
The present thesis approaches the practice of public journalism (PJ) by the press media. The media context in the South of Brazil is called the RBS Phenomenon by Guareschi and Ramos (1988), in which the Zero Hora Newspaper configures a business capitalist model, becoming a strong competitor in the gauchos* media market. In addition to this, according to Faccin (2009) the Rede Brasil Sul (RBS) today is the biggest media network in the South of Brazil, which places it not only as the biggest owner of communication vehicles as a spokesperson of this society. Having this vision of peculiar context we embraced the Zero Hora Newspaper as our empirical object. From state of the art researches we realized that the current of public journalism falls back on a vast number of terms that sometimes are used as synonyms, sometimes used with subtle differences or even with a great variety of applications. Haas (2006) in his studies of worldwide mapping of public journalism elucidates the need of study development that dedicates to deeply investigate the features and peculiarities in different geographic contexts. This way, the problem question which guides this thesis is: How does the public journalism is revealed in journalistic practices at Zero Hora? Accordingly, our general aim is to study the manifestations of public journalism on Zero Hora, and more specifically to comprehend the dynamic of these current journalistic practices on ZH; identify the understanding of journalists in the newsroom as well as the management of this vehicle upon the PJ and confront them with report analysis from news editorial. This thesis is theoretically structured with Rosen (1996), Glaser (1999), Traquina (1999; 2003), Silva (2002; 2006) and Nip (2006). Secondly we treated the media organizations and the journalistic production as of studies by Rodrigues (1990), Esteves (1998), Traquina (1999; 2005), MacQuail (2012; 2013) and McCombs (2009). As a research strategy we adopted the case study (YIN, 2005) and we used different techniques to collect data as well as the document analysis, structured and semi-structured interviews, non-participant systematic observation (MARCONI AND LAKATOS, 2003) and analysis of reports from script elaborated by the researcher. Overall we identified that the journalistic campaign coverage of Fundação Maurício Sirotsky Sobrinho, besides the journalists profiles related directly to the news production, the subject coverage (local and state regional) and the main news values perceived characterize as ways of manifestation of PJ on ZH. This scenery shows that the vehicle has a manifestation potential of this practice. However, ZH stands some organizational gates to this daily journalistic routine making its product oscillate in terms of public journalism which leads us to say that sometimes it is covered and sometimes not.